Odpowiedź :
Cześć!
a)
[tex]x(3x+2)=3(x^2-4)\\\\3x^2+2x=3x^2-12\\\\3x^2+2x-3x^2=-12\\\\2x=-12 \ \ /:2\\\\\huge\boxed{x=-6}[/tex]
b)
[tex]6(1+2x^2)=4x(1+3x)\\\\6+12x^2=4x+12x^2\\\\12x^2-4x-12x^2=-6\\\\-4x=-6 \ \ /:(-4)\\\\\huge\boxed{x=1,5}[/tex]
c)
[tex]3x(x-5)=(3x+2)(x-1)\\\\3x^2-15x=3x^2-3x+2x-2\\\\3x^2-15x=3x^2-x-2\\\\3x^2-15x-3x^2+x=-2\\\\-14x=-2 \ \ /:(-14)\\\\\huge\boxed{x=\frac{1}{7}}[/tex]
Odpowiedź:
a. x(3x+2)=3(x²-4)
3x²+2x=3x²-12
2x=-12 /:2
x=-6
b. 6(1+2x²)=4x(1+3x)
6+12x²=4x+12x²
-4x=-6 /:(-4)
x=6/4=3/2=1 1/2
c. 3x(x-5)=(3x+2)(x-1)
3x²-15x=3x²-3x+2x-2
-14x=-2 /:(-14)
x=2/14=1/7